A Comparative Study of Profile Characteristics Under Different Land Use (Forest, Deforested and Cultivated Lands) in Ranchi - Roy, P.K.; Sahi, B.P.; Alam, S.M (Journal of Soil and Water Conservation, 2022)
The soils under natural vegetation are either natural or only slightly modified natural products. But the soil zone subjected to disturbances by cultivation may undergo a considerable change. Moreso, the increasing use of chemical fertilisers and soil amendments create altogether a different chemical environment in soil.Therefore, it becomes necessary to know that in what respect the inherent properties of the natural soil under forest have changed due to deforestation and subsequent cultivation.